Symbiotic Potential of Soil Microorganisms in Promoting the Growth of Atlantic Forest Tree Species - Santos, Thainá Alves dos; Silva, Felipe Ferreira da; Faria, Sergio Miana de; Chaer, Guilherme Montandon (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
The objective of this study was to evaluate the potential of topsoil obtained from a natural forest fragment in the Brazilian Atlantic Forest to serve as a source of symbiotic microorganisms capable of promoting the growth of native tree species in ecological restoration projects. In greenhouse conditions, 14 experiments in a completely randomized design were conducted in 1,700 cm³ pots filled with sterilized substrate. The effect of adding 80 g of topsoil, either in natura or sterilized, to the substrate was tested on the growth of 14 tree species. Plant height, stem diameter, mycorrhizal colonization and dry masses of shoot, roots, and nodules of tree species were measured. Applying the topsoil to the pots generally resulted in significant increases in height and stem diameter of seedlings compared to the control group during the three to six-month evaluation period. This effect was particularly greater in the nodulating species Plathymenia reticulata, Dalbergia nigra and Mimosa bimucronata, with increases in height and stem diameter of up to 328% and 484%, respectively. Forest topsoil also had a positive impact on the growth of shoot, roots, and nodules of the plants, significantly differing from the control groups. Only the plants that received the topsoil in natura exhibited mycorrhizal colonization and the formation of nodules in nitrogen-fixing species. These plants that established mycorrhizas and nodules presented higher concentrations of phosphorous and nitrogen in their biomass, respectively. Under controlled conditions, the use of forest topsoil proved to be a promising strategy for the introduction of microorganisms that can enhance the growth of tree species, thereby holding potential for implementation in nurseries and field settings.